Sistem Informasi Pembelian Suku Cadang di PT Fuboru Indonesia - Wiria Chandra; Eddy Triswanto Setyoadi; Richard Soegito (LPPM UBHINUS MALANG, 2022)
Purchasing an item from a supplier is an important element for companies to procure goods. Because in a purchase there are so many things that must be considered such as the quality of the goods, the quantity of the goods, the prices of the goods, and many other attributes of the goods which later the goods will be resold to the customers. One company that has a business process/purchase cycle to suppliers is PT. Fuboru. But until now PT. Fuboru in the process of purchasing to suppliers and management of goods in the warehouse still uses the manual method, namely by recording purchases/procurement of goods using books and purchase notes, often loss occurs because the storage of purchase notes is still in the form of archives, causing the absence of systematic purchase data records. This causes problems in service to customers because if there is an error in calculating the stock manually / not computerized, then if there are goods that are out of stock, the procurement of goods will not be carried out immediately, it will take time in the process of procuring goods to suppliers. So that a system is needed that can facilitate the Warehouse and purchasing department to place an order for goods and monitor the stock of goods in the Warehouse. In this research will be made a web-based purchasing information system at PT. Indonesian Fuboru. The information system created can store data on supplier purchase transactions made and management of goods in the warehouse of PT. Fuboru Indonesia. In addition, it can facilitate PT Fuboru Indonesia in monitoring the purchase and management of goods in the warehouse. The research uses the waterfall software development method and uses the PHP (Hypertext Preprocessor) programming language. By using the waterfall software development method, it can facilitate researchers in building information systems because the system is carried out in stages starting from gathering requirements to implementation. Each stage is carried out optimally before the next stage so as to minimize errors